Menggagas Pendidikan Islam Holistik melalui Integrasi Ilmu Pengetahuan dan Spiritualitas - Hasan, Zainol; Nasution, Muhammad Ali Azmi; Asfahani, Asfahani; Muhammadong, Muhammadong; Syafruddin, Syafruddin (Civiliza Publishing, Indonesia., 2024)
Islamic education as the main pillar in shaping the identity and character of Muslims continues to develop along with changing times. Amid the dynamics of modern society, the challenges to Islamic education are increasingly complex, requiring innovation and adaptation to remain relevant and effective. This article aims to initiate holistic Islamic education by integrating science and spirituality as a strategic step in responding to the demands of the times and building a generation of quality Muslims. Through a Systematic Literature Review (SLR) approach, this research investigates related literature to identify knowledge gaps and challenges in implementing holistic Islamic education. The research results reveal that Islamic education models that separate science and spirituality tend to be less effective in forming balanced character and personality in Muslim individuals. This analysis also juxtaposes findings with previous research and holistic educational theories, highlighting the need to develop consistent guidelines and conceptual models. The conclusion emphasizes that holistic Islamic education through the integration of science and spirituality is not only an innovative concept but also an urgent need to produce a generation of Muslims who excel academically and have deep moral awareness in accordance with Islamic principles. This article contributes to critical thinking and renewal in Islamic education in the modern era.